Toksisitas Ekstrak Kulit Batang Kalangkala (Litsea angulata) Terhadap Larva Udang (Artemia salina) dan Identifikasi Senyawa Metabolit Sekundernya - Alvindra Ramadhan; Cahya Anggita Safitri; Endang Astuti; Nur Baiti Athiyah; Tasya Surta Yosya; Farah Erika (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2021)
This study was conducted to determine the content of organic compounds that have been synthesized in the bark extract of the Kalangkala tree (Litsea angulata) and the toxicity of the extract to the larvae of Artemia salina Leach shrimp. BST (Brine Shrimp Lethality) method was used as a preliminary test to obtain ethanol extract and n-hexane extract of Kalangkala tree bark (L. angulata) which were toxic with LC50 values of 647 ppm and 907 ppm, respectively. The results of phytochemical screening also showed that the bark extract of the Kalangkala (L. angulata) tree contains saponins and steroids. Keywords: Kalangkala, Litsea angulata, phytochemical screening, toxicity.